Printed Versus Electronic Texts in Inclusive Environments: Comparison Research on the Reading Comprehension Skills and Vocabulary Acquisition of Special Needs Students - Özlem Dağlı Gökbulut; Ahmet Güneyli (MDPI AG, 2019)
In this research, an effort is made to compare the effectiveness of reading texts presented through electronic books in a computer environment and regular (printed) texts, in terms of the development of the reading comprehension and vocabulary acquisition skills of students with special needs within inclusive educational environments. The research was designed with ‘Adaptive Alternating Applications’, and the study group of the research was formed by using the ‘purposive sampling’ method. As a requirement of the research design used, two special needs students were studied. According to the results of the study, the vocabulary acquisition levels of both students produced more effective results in presentations made with electronic texts, and in addition, electronic texts were found to be more effective in improving reading comprehension skills than printed texts.